Cytokine levels in febrile seizure patients: A systematic review and meta-analysis. (July 2018) - Kwon, Aram; Kwak, Byung Ok; Kim, Kyungmin; Ha, Jongseok; Kim, Soo-Jin; Bae, Sun Hwan; Son, Jae Sung; Kim, Soo-Nyung; Lee, Ran
Highlights: There are many studies about cytokine levels and febrile seizures(FS). The association between cytokine levels and FSs is inconclusive. This study shows FS patients have significantly higher CSF IL-1β and serum IL-6 levels. Abstract: Purpose: Febrile seizures (FSs) are the most common form of childhood seizures. During infection, both pro-inflammatory and anti-inflammatory cytokines are produced. Complex interactions among immune-inflammatory process, cytokine activation, and genetic factors are involved in the pathogenesis of FSs. The association between cytokines and FSs during childhood is inconclusive due to inconsistent results reported in different studies. We performed a systematic review and meta-analysis to determine an association between cytokines and FS in children. Methods: We searched PubMed, EMBASE, and Cochrane databases for studies published up to January 2017 using the following key words: ["cytokine" OR "interleukin" OR "tumor necrosis factor alpha" OR "interferon-gamma" OR "single nucleotide polymorphism"] AND ["febrile seizure" OR "febrile convulsion"] AND ["pediatric" OR "infant" OR "child"]. Standardized mead difference (SMD) and 95% confidence intervals (CI) were calculated using standard meta-analysis techniques. Results: A total of 6 studies enrolling 243 children with FS and 234 controls were included in the meta-analysis. A total of 4 different inflammatory mediators were. The results indicated that CSF IL-1β level and serum IL-6 level were significantly associated with FS (CSF IL-1β: SMD, 1.064; 95% CI, 0.217–1.611; P < 0.01, serum IL-6 SMD, 2.654; 95% CI, 2.332–2.975; P < 0.01). Conclusion: The results of this meta-analysis suggest that CSF IL-1β level and serum IL-6 level are associated with an increased risk of FSs in children. Based on these results, it is expected that a therapeutic agent for specific cytokines could be developed in the future to prevent FS.